Application of storytelling in communication of organisations - Siudikienė, Daiva (Information & Media, 2016)
The purpose of this article to reveal the corporate storytelling usability in organisational communication. The paper analyses the most important aspects of its application to increase the target groups interests and their involvement in the organisation’s communication. In contemporary business organisations, communication corporate stories are defined as one of the effective strategies to control the huge flow of information, give it a clear and attractive form and create a unique and memorable image of the organisation for its target audiences. After the analysis of scientific literature, it was stated that storytelling is an integral part of successful activity of organisation not only in creating the image of the organisation inside and outside, but also in ensuring the smooth functioning of the work, motivating the employees, strengthening the organisational culture, sharing the knowledge etc. It was stated that the importance of corporate storytelling is growing in the participatory culture context. Contemporary organisations seek more attractive forms of communication and represent visual and interactive stories in the multimedia environment instead of facts or other quantitative indicators. This technique does not deny the importance of the facts, figures or schemes, but it fosters to look more carefully at the business strategy and to link the strategic goals with the social context and the problems of the target audiences
Keywords: ...